Ecofeminism in the Framework of Local Wisdom: Viewing the Existence of Mpu Uteun as a Forest Guardian - Qabilla, Nayyara Shafa; Abulkhair, Muhammad Faris; Nabila, Siti; Jemany, Jemany; Riamanda, Irin (Journal of Governance and Social Policy, 2024)
Environmental degradation, such as illegal logging and poaching, has caused significant harm, particularly to communities dependent on forests. Women, who share an intimate connection with nature through needs like water, food, and shelter, are among the most affected groups. In this context, ecofeminism emerges to advocate for equality and challenge the domination of women and nature. A manifestation of ecofeminism is seen in the Mpu Uteun community in Damaran Baru, Bener Meriah Regency, led by women. This qualitative study employs a phenomenological approach, with five respondents selected through purposive sampling. The findings reveal four key themes: Nature Dependency (human reliance on nature), Feminine Competence (women's ability to protect forests), Recognition (acknowledgment of Mpu Uteun), and Existence (the community's well-being). These insights highlight the role of women as forest guardians and significant agents of change within the ecofeminism framework.Therefore most of them prefer to invest in businesses rather than this UPS retirement scheme.